CREATIVE TRAINING IN CULTURAL PRESERVATION: REPACKAGING MENTAWAI CUSTOMARY KNOWLEDGE FOR EDUCATIONAL MEDIA AND SOCIALIZATION - Hasfera, Dian; Zulfa, Zulfa; Sabaggalet, Yudas; Marfi, Zahra Lathifah; Isdarwanti, Indri (Bhandar: Harvesting Community Service in Asia, 2025)
This community service aims to describe the process and impact of creative training in an effort to preserve culture through repackaging the indigenous knowledge of the Mentawai people into educational and socialization media. The background of this research is based on concerns about the fading of local cultural values due to the flow of globalization and the lack of documentation and delivery of indigenous knowledge to the younger generation. The method of implementing this activity is carried out to provide solutions in order to overcome partner problems. Through needs analysis, work plans, activity implementation and evaluation. Activities realized in community service include: providing material on creative training in an effort to preserve culture through repackaging the indigenous knowledge of the Mentawai people. Based on the results of technological guidance, descriptions of the results and discussions of this activity, it can be concluded that with this creative training, the Mentawai people, especially the younger generation who participated in creative training involving local artists, traditional figures, and youth, were able to create educational media such as documentary videos, cultural infographics, and interactive performances that are easy to understand and interesting for teenagers. In addition to increasing awareness of the importance of cultural preservation, this activity also encourages active community participation in the process of inheriting indigenous values. Thus, repackaging indigenous knowledge through a creative approach is an effective strategy in maintaining local cultural heritage in the modern era.